Progress report of POLEX-South programme in 1980 by the 21st Japanese Antarctic Research Expedition - Shun'ichi Kobayashi; Nobuyoshi Ishikawa; Tetsuo Ohata; Sadao Kawaguchi (National Institute of Polar Research, 1982)
In 1980,the present authors in the 21st Japanese Antarctic Research Expedition carried out glacial-meteorological observations at Mizuho Station and Syowa Station as the second year programme of the Japanese POLEX-South. Items of observation at Mizuho Station (70°42′S, 44°20′E, 2230m above sea level) were : 1) observations of surface boundary layer by a 30m high observation tower, 2) radiation budget, 3) low level radio-sondes, 4) sonic-wave sounder, 5) measurements of sensible heat flux by sonic-anemometer, 6) blowing snow, 7) snow accumulation by sonic-wave snow depth meter and 8) surface synoptic weather. In the vicinity of Syowa Station (69°00′S, 39°35′E, on East Ongul Island), the following studies were carried out : 1) heat budget of sea ice, 2) observation of surface inversion layer by sonic-wave sounder, 3) meteorological observations by an unmanned weather station, 4) airborne survey of radiation budget, surface radiation temperature and surface morphology, and 5) observations of frazil ice. This paper mainly describes the installation and performance of the measurement system and preliminary results.